INVESTIGATING STUDENTS’ LEARNING STYLE BY USING VAK MODEL - Deni Asrida (Pusat Pengembangan Bahasa IAIN Tulungagung, 2019)
This study was aimed to investigate students learning style of the second semester students of English Department of IAIN Batusangkar in 2017/2018 academic year. The design of this research was descriptive quantitative. In collecting the data, the researcher used questionnaires which was constructed according to the indicators gotten from the theories. Meanwhile, to see the validity and reliability of the questionnaire, it was tried out to some selected respondents. In analysing the data, the researcher used SPSS 21 for descriptive analysis. Based on the data analysis, it was found two students tend to have visual learning style or 3,5%. Meanwhile, 39 students have auditory learning style 68,42% and 16 students have a tendency kinesthetic learning style 28,7%. It is also can be seen that most of students, 68,42%, have auditory learning style as the dominant learning style.